Measurement of Air-Sea Methane Fluxes in the Baltic Sea Using the Eddy Covariance Method - Gutiérrez-Loza, Lucía; Wallin, Marcus B.; Sahlée, Erik; Nilsson, Erik; Bange, Hermann W.; Kock, Annette; Rutgersson, Anna (Frontiers in Earth Science, 2019)
Methane (CH4) is the second-most important greenhouse gas in the atmosphere having a signiﬁcant effect on global climate. The ocean—particularly the coastal regions—have been recognized to be a net source of CH4, however, the constraints on temporal and spatial resolution of CH4 measurements have been the limiting factor to estimate the total oceanic contributions. In this study, the viability of micrometeorological methods for the analysis of CH4 ﬂuxes in the marine environment was evaluated. We present one year of semi-continuous eddy covariance measurements of CH4 atmospheric dry mole fractions and air–sea CH4 ﬂux densities at the Östergarnsholm station at the east coast of the Gotland Island in the central Baltic Sea. The mean annual CH4 ﬂux density was positive, indicating that the region off Gotland are a net source of CH4 to the atmosphere with monthly mean ﬂux densities ranging between -0.1 and 36 nmol m−2s−1. Both the air–water concentration gradient and the wind speed were found to be crucial parameters controlling the ﬂux. The results were in good agreement with other measurements in the Baltic Sea reported in the MEMENTO database. Our results suggest that the eddy covariance technique is a useful tool for studying CH4 ﬂuxes and improving the understanding of air-sea gas exchange processes with high-temporal resolution. Potentially, the high resolution of micrometeorological data can increase the understanding of the temporal variability and forcing processes of CH4 ﬂux.